2022
DOI: 10.1186/s13054-022-04260-1
|View full text |Cite
|
Sign up to set email alerts
|

Association between cholinesterase activity and critical illness brain dysfunction

Abstract: Background Delirium is a frequent manifestation of acute brain dysfunction and is associated with cognitive impairment. The hypothesized mechanism of brain dysfunction during critical illness is centered on neuroinflammation, regulated in part by the cholinergic system. Point-of-care serum cholinesterase enzyme activity measurements serve as a real-time index of cholinergic activity. We hypothesized that cholinesterase activity during critical illness would be associated with delirium in the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…There is a vast array of biomarker literature in post‐operative and critical care delirium. Biomarkers that have been reported in a critical care population including neurofilament light protein (NfL), serum C‐reactive protein (CRP), interleukin (IL)‐1, IL‐6, IL‐8, and IL‐10, plasma tau, neuron‐specific enolase (NSE), and most recently acetylcholinesterase, which was reported by Hughes et al in 2022 10,45 …”
Section: Precision Phenotypes Biomarkers and Delirium In Critical Ill...mentioning
confidence: 99%
See 2 more Smart Citations
“…There is a vast array of biomarker literature in post‐operative and critical care delirium. Biomarkers that have been reported in a critical care population including neurofilament light protein (NfL), serum C‐reactive protein (CRP), interleukin (IL)‐1, IL‐6, IL‐8, and IL‐10, plasma tau, neuron‐specific enolase (NSE), and most recently acetylcholinesterase, which was reported by Hughes et al in 2022 10,45 …”
Section: Precision Phenotypes Biomarkers and Delirium In Critical Ill...mentioning
confidence: 99%
“…Based on their findings, the authors concluded that NfL measurement within the first 3 days of admission may be useful to identify those patients with worse clinical outcomes and serve as a valuable tool for investigating future delirium interventions. In 2022, Hughes et al 45 reported a landmark delirium biomarker study where they hypothesized that higher acetylcholinesterase (AChE) activity would be an indication of delirium presence in ICU. The authors enrolled 272 ICU patients and compared AChE activity in patients with delirium versus normal mental state.…”
Section: Precision Phenotypes Biomarkers and Delirium In Critical Ill...mentioning
confidence: 99%
See 1 more Smart Citation
“…Reexamining cholinesterase inhibitors for the prevention and treatment of delirium in high-risk populations Ori J. Lieberman 1* , Vanja C. Douglas 1 and Sara C. LaHue 1,2 We read with interest the article Hughes et al recently published in Critical Care describing the correlation between circulating levels of acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) activity in critically ill adults and their risk of delirium or coma [1]. The implementation of a point-of-care testing paradigm for serum AChE and BChE activity raises the possibility of identifying a population at high risk of developing delirium for future clinical trials.…”
mentioning
confidence: 99%
“…Designing such a clinical trial would necessitate identifying a population at high risk for developing delirium. At ICU admission, the use of rapid point-of-care testing for the measurement of serum AChE and BChE activity, such as that reported by Hughes et al [1], or selection of those with co-existing cognitive impairment [15], could be used to further enrich a population with a cholinergic deficit. Randomization to AChEi initiation or placebo could then occur and in-hospital and post-discharge outcomes would be collected.…”
mentioning
confidence: 99%